Faktor Bauran Pemasaran Yang Mempengaruhi Konsumen Terhadap Keputusan Pembelian Produk Pada Konsumen Starbucks Coffee - Arief Satriansyah (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
This research was conducted to find out how much influence of the product, price, place and promotion on Starbucks Coffee Bogor city consumers' decision making. The research used the survey method with a sample of 100 people. The sampling technique is non-probability sampling: judgment sampling. The analytical method used is the method of correlation analysis and multiple regression. The results of the study show that both partially and jointly the factors of product, price, place, and promotion have a significant influence on product purchase decision making. The higher the level of influence of the product, price, place and promotion, the stronger the influence of product purchasing decisions. Based on the results of the analysis of the factors that influence the purchasing decision shows the adjusted R2 value of 0.663, this means that all variables derived from the marketing mix have a joint contribution of 66.3% to the dependent variable (Y), namely the purchasing decision. The remaining 33.7% is influenced by other factors.